Literature Review: K-Beauty Effect on Health Behavior and Korean Cosmetics Purchasing in Indonesia - Rachmawati Widyaningrum; Khairunisa Ramadhani; Budi Lestari (Disease Prevention and Public Health Journal, 2023)
Background: The K-wave popularity led to increased Korean fans in Indonesia, including other sectors of Korean products. Further, the styles of the stars, look, and culture became Indonesian people's references in fashion, ideal body shape, and food consumption patterns. However, a concern was also raised about the halal status of Korean beauty products and Indonesian health behavior to meet the ideal body shape of Korean celebrities. This study aims to understand the general perspective of the K-beauty popularity effect on Indonesian people's health behavior and cosmetics purchasing intention, including its halal issues. Method: This study was conducted by reviewing relevant research articles between 2012 to 2022 on the topic through a google scholar search engine. In total, 14 articles that meet the inclusion criteria were reviewed. Results: This study found that some adolescents that worshiped Korean idols had a negative body image and did a strict diet, heavy exercise, took weight loss pills, or did plastic surgery to meet their body goals. Further, South Korean dramas significantly affect the brand image of Korean cosmetics and further increase its purchasing intention. People's knowledge of halal cosmetics, religion, and the halal label will affect their purchasing level and preference for halal cosmetics. Conclusions: This study concludes that the emerging K-beauty trend should be balanced with the knowledge about a healthy way to gain beauty and the understanding of halal cosmetics. The stakeholder should enhance the intervention to improve youngsters' knowledge and attitude toward halal cosmetics and a healthy diet.